Circular RNA_0003489 reflects unfavorable treatment response and shortened survival in newly diagnosed multiple myeloma patients who receive bortezomib-based induction therapy - Senhua Song; Junjie Xie; Biao Xu; Qijie Ran (Hematology)
Objectives Circular RNA_0003489 (Circ_0003489) promotes multiple myeloma (MM) progression and bortezomib resistance in MM cells, while its potential as a biomarker in newly diagnosed MM (NDMM) patients is unclear. Thus, this study aimed to investigate the association of circ_0003489 expression with treatment response and survival in NDMM patients who received bortezomib-based induction therapy.Methods Bone marrow (BM) specimens from 85 NDMM patients at diagnosis or before treatment and from 15 donor controls during BM examination were retrieved in this retrospective study. Circ_0003489 derived from BM plasma cells was detected by reverse transcription-quantitative polymerase chain reaction and cut by quartile and median for further analysis.Results Circ_0003489 expression was increased in NDMM patients versus donor controls (P < 0.001). Circ_0003489 quartile was positively correlated with BM plasma cells (P = 0.040), international staging system (ISS) stage (P = 0.007), the revision of ISS stage (P = 0.003), beta-2-microglobulin (P = 0.011), and lactate dehydrogenase (P = 0.042) in NDMM patients. Increased circ_0003489 quartile was linked with a lower possibility of achieving complete response (P = 0.020) and partial response or better (P = 0.041) in NDMM patients. Elevated circ_0003489 expression cut by quartile (P = 0.020) and cut by median (P = 0.006) were linked with decreased progression-free survival (PFS) in NDMM patients. Increased circ_0003489 expression cut by median was associated with shortened overall survival (OS) in NDMM patients (P = 0.038). Meanwhile, higher circ_0003489 quartile independently forecasted poorer PFS (hazard ratio = 1.342, P = 0.045), but not OS in NDMM patients.Conclusion Circ_0003489 expression is increased and reflects unfavorable treatment response and survival in NDMM patients who receive bortezomib-based induction therapy.